Transcriptional Profiling in a Novel Swine Model of Traumatic Brain Injury - Samuel S. Shin; Amy C. Gottschalk; Vanessa M. Mazandi; Todd J. Kilbaugh; Marco M. Hefti (Neurotrauma Reports, 2022)
Transcriptomic investigations of traumatic brain injury (TBI) can give us deep insights into the pathological and compensatory processes post-injury. Thus far, transcriptomic studies in TBI have mostly used microarrays and have focused on rodent models. However, a large animal model of TBI bears a much stronger resemblance to human TBI with regard to the anatomical details, mechanics of injury, genetics, and, possibly, molecular response. Because of the advantages of a large animal TBI model, we investigated the gene expression changes between injured and uninjured sides of pig cerebral cortex after TBI. Given acute inflammation that follows after TBI and the important role that immune response plays in neuroplasticity and recovery, we hypothesized that transcriptional changes involving immune function will be upregulated. Eight female 4-week-old piglets were injured on the right hemisphere with controlled cortical impact (CCI). At 5 days after TBI, pericontusional cortex tissues from the injured side and contralateral cortical tissues were collected. After RNA extraction, library preparation and sequencing as well as gene expression changes between the ipsi- and contralateral sides were compared. There were 6642 genes that were differentially expressed between the ipsi- and contralateral sides, and 1993 genes among them had at least 3-fold differences. Differentially expressed genes were enriched for biological processes related to immune system activation, regulation of immune response, and leukocyte activation. Many of the differentially expressed genes, such as CD4, CD86, IL1A, IL23R, and IL1R1, were major regulators of immune function. This study demonstrated some of the major transcriptional changes between the pericontusional and contralateral tissue at an acute time point after TBI in pigs.